Henryk Cholaj, Tradycje akademickie Puław, Puławy 1999, Wydawnictwo Puławskiej Szkoły Wyższej, s. 67 - Kosman, Marceli (Biuletyn Historii Wychowania, 2000)
Henryk Cholaj, Tradycje akademickie Puław, Puławy 1999, Wydawnictwo Puławskiej Szkoły Wyższej, s. 67